2002
DOI: 10.2337/diabetes.51.6.1655
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies of Late Diabetic Complications

Abstract: Genes play a role in many processes underlying late diabetic complications, but efforts to identify genetic variants have produced disappointing and contradictory results. Here, we evaluate whether the study designs and analytic methods commonly being used are optimal for finding susceptibility genes for diabetic complications. We do so by generating plausible genetic models and assessing the performance of case-control and family-based trio study designs. What emerges as a key determinant of success is durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…Specifically, the Ͻ24-yr duration group exhibited excess transmission of the T-G haplotype, whereas the Ն24-yr duration group exhibited deficient transmission of the same haplotype. This is precisely the pattern we would expect for a broad class of genetic models of diabetic nephropathy in which the duration of diabetes mellitus is important (19).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Specifically, the Ͻ24-yr duration group exhibited excess transmission of the T-G haplotype, whereas the Ն24-yr duration group exhibited deficient transmission of the same haplotype. This is precisely the pattern we would expect for a broad class of genetic models of diabetic nephropathy in which the duration of diabetes mellitus is important (19).…”
Section: Discussionsupporting
confidence: 63%
“…The cutoff value of 24 yr was determined a priori, on the basis of previously recorded information on the median diabetes mellitus duration (20), as described in Materials and Methods. The rationale for this stratification was to identify patients with shorter diabetes mellitus duration at the onset of proteinuria, because we previously demonstrated that this group was ideal for the identification of nephropathy genes (19). Lacking a direct estimate of the duration of diabetes mellitus at the onset of proteinuria, we chose to use the diabetes mellitus duration at the time of enrollment for patients with proteinuria and the duration at the initiation of dialysis for those with ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations